miR-183-5p Aggravates Breast Cancer Development via Mediation of RGS2 - Chihua Wu (Hindawi Limited, 2021)
This study mainly explores how miR-183-5p pertains to breast cancer (BC) development. Functional assays were employed to test impacts of miR-183-5p in this cancer. Targeting between RGS2 and miR-183-5p was examined with dual-luciferase assay, and how their interaction pertains to cancer progression was further unraveled. miR-183-5p level was noticeably high in cancer tissue/cells. Overexpressing miR-183-5p could remarkably deteriorate cancer progression. The regulatory gene RGS2 levels was markedly low in BC, and two genes we researched were negatively correlated. It was uncovered by rescue assay that miR-183-5p/RGS2 axis mediated tumor-relevant behaviors in BC. Altogether, miR-183-5p aggravates BC development via mediation of RGS2. miR-183-5p supplies a promising target for BC therapy.